2020
DOI: 10.4314/acsj.v28i1.16s
|View full text |Cite
|
Sign up to set email alerts
|

Status of vegetative propagation of baobab: A review

Abstract: The African baobab (Adansonia digitata L.) is a large tree of great socio-economic and cultural importance in Africa, with almost all the parts of the species used for various purposes. A major concern about baobab fruit pulp production is the long time it takes for first fruiting (about 15 years). Vegetative propagation offers several advantages with regard to consumers’ preferences and precociousness of fructification. The objective of this study was to synthesise existent knowledge related to vegetative pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Jensen et al (2011), reported anthesis in baobab to be between eight and twenty-three (8-23) years when planted by seed or three to five (3-5) years when grafted. However, in recent publication, Agbohessou et al 2020 stated that result of grafted baobab to fruiting has not yet been documented. There are two similar but different issues here.…”
Section: Observations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jensen et al (2011), reported anthesis in baobab to be between eight and twenty-three (8-23) years when planted by seed or three to five (3-5) years when grafted. However, in recent publication, Agbohessou et al 2020 stated that result of grafted baobab to fruiting has not yet been documented. There are two similar but different issues here.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…Vegetative propagation methods thus need to be explored to reduce the maturity period of the plant to attract farmers to cultivate it. Vegetative propagation also results in producing true to type plants and will be particularly important in baobab to help manage wide diversity that could result from seed propagation (Agbohessou et al , 2020). The vegetative methods ever reported in baobab include grafting, cutting and in vitro propagation (Agbohessou et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To take advantage of the high intraspecific phenotypic and genetic variation within and between populations, vegetative propagation techniques have many advantages. One study reviewing the literature on the use of vegetative propagation in baobab reported only 30% rooting success with IBA hormone [76] and recommended the need for further studies, especially for the rooting of cuttings and marcotting. Anjarwalla et al [77] and Jenya et al [40], however, reviewed 'top cleft' and 'side veneer' grafting techniques in Kenya and Malawi.…”
Section: Domesticationmentioning
confidence: 99%
“…Vegetative propagation is used to capture elite phenotypes as putative cultivars and has been evaluated in a number of important tree species in the region, including Prosopis africana [433], Argania spinosa [435,436], B. aegyptiaca [437,438], A. digitata [76] and V. paradoxa [136]. For instance, in Niger, Prosopis africana has been found to be amenable to air layering with no significant differences between the diameter classes and between the positions, although the success rate was low (28% after 4 months) [439].…”
Section: Vegetative Propagationmentioning
confidence: 99%
“…e above-mentioned strategies require good quality seeds, which are propagated from trees either generatively or vegetatively. Vegetative propagation has the advantage of producing plants with traits similar to the mother plant [19,20]. e selection of mother plants as a source of plant material in vegetative propagation is pivotal in the success of S. benzoin cultivation.…”
Section: Introductionmentioning
confidence: 99%